Perception of occupational health hazards and injuries among construction workers: A case study of residential construction company - Jarukkhamool, Sutprattana; Chaiklieng, Sunisa (Asia-Pacific Journal of Science and Technology, 2017)
This survey study aimedto investigate the awareness ofoccupational health hazards from the working conditions ofconstruction workers by using a case study ofresidential construction company. All 80 subjects were construction workers. Data were collected by an interviewed questionnaire for experience of health problems from working activities andgathering numbers of accidents from construction work. The results showedthatthe major health problem was the musculoskeletal disorders. The following health problems were the respiratory health symptoms (i.e. coughing, diffiulty breathing, wheezing) and skinrash which was complained in workers with plasterfunction. Foroccupational injuries, there were six cases peryear. The mostsevere level was atmild injury with lost work time for less than one hour (50%). The Injuries frequency rate (IFR) was 31.25 and the Injury Severity Rate (ISR) was 169.27. The average severity ofinjury was 5.42. In conclusion, there were quite high evidence o fsubclinical symptoms and occupational injuries among residential construction workers. The company should run risk assessment on occupation injuries in every process of construction work in order to initiate the safety working project and health surveillance program among construction workers.